2021
DOI: 10.1111/ans.16771
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular reconstruction of head and neck defects in the elderly

Abstract: Background Microvascular free‐flap reconstruction of the head and neck is a common technique utilized across many ages. The purpose of this study was to identify if advanced age or comorbidity was associated with worse post‐operative outcomes in patients undergoing free‐flap reconstruction. Methods A retrospective analysis was performed on 344 consecutive patients undergoing free‐flap surgery of the head and neck. Demographic, clinical and pathological factors were considered along with Charlson Comorbidity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In a study examining the effect of advanced age on post‐operative outcomes in the, Every et al . found that elderly patients (in this case, those aged above 75 years) had a higher overall complication rate (odds ratio 1.7) that was restricted to medical complications (odds ratio 2.1) and not surgical complications 45 . Other studies have shown similar data, confirming the relationship between elderly patients and postoperative medical complications 15,16 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In a study examining the effect of advanced age on post‐operative outcomes in the, Every et al . found that elderly patients (in this case, those aged above 75 years) had a higher overall complication rate (odds ratio 1.7) that was restricted to medical complications (odds ratio 2.1) and not surgical complications 45 . Other studies have shown similar data, confirming the relationship between elderly patients and postoperative medical complications 15,16 .…”
Section: Discussionsupporting
confidence: 71%
“…In a study examining the effect of advanced age on post-operative outcomes in the, Every et al found that elderly patients (in this case, those aged above 75 years) had a higher overall complication rate (odds ratio 1.7) that was restricted to medical complications (odds ratio 2.1) and not surgical complications. 45 Other studies have shown similar data, confirming the relationship between elderly patients and postoperative medical complications. 15,16 Islam and Badry's retrospective study on postoperative complications in elderly patients undergoing surgery for HNC treatment also found a significant link between the elderly and medical complications, yet not surgical complications.…”
Section: Discussionsupporting
confidence: 62%
“…Despite high overall free‐flap success rates, complications following head and neck free‐flap reconstruction remain common. Of these, the most common surgical complications include dehiscence, fistula, infection, hematoma, and flap compromise 29,30 . Additionally, intraoperative holdups remain a common cause for delay, adding to operative time, anesthesia time, and OR costs.…”
Section: Free‐flap Closure Timeoutmentioning
confidence: 99%
“…Of these, the most common surgical complications include dehiscence, fistula, infection, hematoma, and flap compromise. 29,30 Additionally, intraoperative holdups remain a common cause for delay, adding to operative time, anesthesia time, and OR costs. Previous authors have estimated average operating room costs to equal $66 per min, which are likely to be even higher in complex surgeries such as head and neck free-flap reconstruction.…”
Section: Free-flap Closure Timeoutmentioning
confidence: 99%